Achievements, challenges and perspectives of civic education, education for democratic citizenship and education in human rights. A theoretical and bibliographical-historical overview - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2024)
A conceptual representation of what civic education means is made taking into account the approach of the Constitution, the regulation in the organization and curriculum of the educational system, the recommendations of the European Union, the vision of UNESCO and the academic theoretical treatment. The Constitution relates education with fundamental rights and freedoms and the democratic principles of coexistence. The European Parliament and the Council have sufficiently defined what civic social competence, education for democratic citizenship and education in human rights entail. UNESCO advocates for an Education for Global Citizenship. Authors who have carried out research and theoretical studies on the concept of civic education are described. All these contributions serve to define the characteristics and identifying features of what civic education entails, and a definition is reached that brings together, in a joint proposal, civic education, together with the terms education for democratic citizenship and human rights. The diagnosis and analysis of the situation of civic education is presented, taking into account the contributions of national and international organizations, research, testimonies of academics and bibliometric analysis. There has been progress in this democratic stage of our country but there are important challenges in the institutional, political, regulatory and educational fields. Different perspectives and approaches to civic education are raised: historical-legal; educational and curricular; European and international; political; jurisdictional; and associative. The final considerations raise the urgent need for civic education to alleviate and to give response to serious existing problems (racism, xenophobia, segregation, political disaffection, corruption, threats to democracy, unemployment, violence against women, poverty and social exclusion, etc.). To do this, it is necessary that civic education is not only the responsibility of the school but of the whole society.